Distribution, temporal stability and association with all-cause mortality of the 2017 GOLD groups in the ECLIPSE cohort. (August 2018) - Faner, Rosa; Noell, Guillaume; Badia, Joan Ramon; López-Giraldo, Alejandra; Bakke, Per; Silverman, Edwin K.; Tal-Singer, Ruth; Agustí, Alvar
Abstract: Background: In 2017, the Global Initiative for Chronic Obstructive Lung Disease (GOLD) proposed a new classification of patients with chronic obstructive pulmonary disease (COPD). Material and methods: We contrasted the distribution of COPD patients according to GOLD 2017 and 2011 classifications, the temporal stability of the 2017 groups during 3 years follow-up and their association with all-cause mortality in the ECLIPSE cohort. Results: We found that GOLD 2017: (1) switched a substantial proportion of GOLD 2011C and D patients to A and B groups at recruitment; (2) about half of A, B and D patients remained in the same group at the end of follow-up, whereas 74% of C patients (the smallest group of all) changed, either because exacerbation rate decreased or dyspnea increased; and, (3) all-cause mortality by group was not significantly different between GOLD 2011 and 2017. Of note, mortality in B (16%) and D patients (18%) was similar, both with similar severity of airflow limitation, the best individual mortality risk factor. Conclusions: These results illustrate the cross-sectional and longitudinal effects of excluding FEV1 from GOLD 2017, and highlight both the clinical relevance of symptom assessment in the management of COPD and the prognostic capacity of FEV1. Highlights: Many C/D patients according to GOLD2011 are moved to A/B groups by GOLD2017. C patients (GOLD2017) are the less prevalent and stable through time. Mortality by group was not significantly different between GOLD 2011 and 2017.